Facilitação como atenuante do estresse ambiental entre populações microbianas imobilizadas - Martins, Suzana Cláudia Silveira (2012)
The attenuating influence of facilitate or positive interactions between immobilized and associated microbial populations under environmental stresse conditions is the main objective of this study. In this perspective, five chapters were developed. The first shows the state of the art of microbial immobilization, importance of facilitating interactions between species under environmental stress and cell immobilization as a tool to increase the efficiency of treatment of toxic pollutants in industrial wastewaters. In the second chapter was defined the type of polyurethane foam and the culture medium to be used for natural immobilization. In the third, qualitative and quantitative tests were conducted for selection of environmental microbial strains with potential for cell adhesion. The fourth chapter consisted of the evaluation of the effect of environmental stress on microbial populations immobilized in monoculture. In the fifth and last chapter, the selected microbial strains were immobilized in consortium and tested the effect of a physiological stress on the adaptive value of microbial populations, indicative of the predominant type of interaction between the species. The potential of strains for biotransformation processes of toxic chemical pollutants was also investigated. The results showed polyurethane foam of 23 kg/m3 immersed in Luria-Bertani broth diluted ten fold, as appropriate for cell retention of about 107 cells of Pseudomonas aeruginosa ATCC 25619. Among environmental microbial strains the Serratia marcescens bacterium and the yeast C. rugosa showed better adhesion potential. Individual microbial cells immobilized on polyurethane foam were more resistant to phenol than the respective cell suspensions. When associated, the two strains showed better adaptive value in the presence of phenol, compared to the same cells immobilized in individual cultivation, proving the prevalence of facilitative interactions between microbial populations.